School food policies and the transition of urban food systems in Brazil and France: insights from São Paulo and Greater Paris region case studies - Retière, Morgane; Darly, Ségolène (Frontiers in Sustainable Food Systems, 2023)
For many promoters of alternative food systems, scaling up local food provisioning holds the promise of mitigating the negative impacts of the corporatist’s food sector by stimulating regional agricultural diversification. Although these initiatives challenge the dominant model, the question remains of their transformative power and their place in the dynamics of change, at the meso and macro levels. School catering is often seen as a sector where these doubts can be overcome. In this paper, we seek to explore the role of national political engagement encouraging school food sustainable procurement in framing the possibilities for scaling up alternative’s impacts on agricultural landscapes. In highly urbanized countries, larger cities urban food strategies are expected to contribute significantly to bending the curve of landscape simplification. Based on the analysis of the day-to-day governance of school food procurement in 21 case studies located in Greater Paris and São Paulo, our findings mitigate this enthusiasm. We show that most cases relate to the trend of a dominant alternative pattern that relies on a renewed agro-industrial system which do not challenge the regional specialization dynamics. Nevertheless, most of the cases that deviate significantly from this model are found in the São Paulo metropolitan area, suggesting that national framework can still set the conditions for local innovations.